PENGARUH FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM - santa, santa ompusunggu; Setiawati, Erni; Yanti, Novi; Milanda, Devy Putri (OBOR: Oikonomia Borneo, 2024)
This study aims to analyze the impact of fundamental factors, namely Earnings Per Share (EPS), Price to Book Value (PBV), Return on Equity (ROE), and Debt to Equity Ratio (DER) on stock prices of companies in the food and beverage sector listed on the Indonesia Stock Exchange during the period of 2019-2022. The research utilizes a quantitative approach with data analysis conducted using SPSS software version 24. The results indicate that EPS and PBV have a positive significant effect on stock prices, suggesting that strong earnings per share performance and a higher market value relative to book value attract investor interest. In contrast, ROE negatively affects stock prices, indicating that poor financial performance or low efficiency in capital utilization reduces investor confidence. Meanwhile, DER has no significant impact on stock prices, as investors are more concerned with how a company utilizes its debt for operations. This study provides valuable insights for investors in making investment decisions based on the fundamental analysis of companies